Rapid diagnostic tests duo as alternative to conventional serological assays for conclusive Chagas disease diagnosis. - Karina E Egüez; Julio Alonso-Padilla; Carolina Terán; Zenobia Chipana; Wilson García; Faustino Torrico; Joaquim Gascon; Daniel-Franz; María-Jesús Pinazo (Public Library of Science (PLoS), 2017)
Chagas disease is caused by the parasite Trypanosoma cruzi. It affects several million people, mainly in Latin America, and severe cardiac and/or digestive complications occur in ~30% of the chronically infected patients. Disease acute stage is mostly asymptomatic and infection goes undiagnosed. In the chronic phase direct parasite detection is hampered due to its concealed presence and diagnosis is achieved by serological methods, like ELISA or indirect hemagglutination assays. Agreement in at least two tests must be obtained due to parasite wide antigenic variability. These techniques require equipped labs and trained personnel and are not available in distant regions. As a result, many infected people often remain undiagnosed until it is too late, as the two available chemotherapies show diminished efficacy in the advanced chronic stage. Easy-to-use rapid diagnostic tests have been developed to be implemented in remote areas as an alternative to conventional tests. They do not need electricity, nor cold chain, they can return results within an hour and some even work with whole blood as sample, like Chagas Stat-Pak (ChemBio Inc.) and Chagas Detect Plus (InBIOS Inc.). Nonetheless, in order to qualify a rapidly diagnosed positive patient for treatment, conventional serological confirmation is obligatory, which might risk its start. In this study two rapid tests based on distinct antigen sets were used in parallel as a way to obtain a fast and conclusive Chagas disease diagnosis using whole blood samples. Chagas Stat-Pak and Chagas Detect Plus were validated by comparison with three conventional tests yielding 100% sensitivity and 99.3% specificity over 342 patients seeking Chagas disease diagnosis in a reference centre in Sucre (Bolivia). Combined used of RDTs in distant regions could substitute laborious conventional serology, allowing immediate treatment and favouring better adhesion to it.